2015
DOI: 10.1037/a0037908
|View full text |Cite
|
Sign up to set email alerts
|

Condoning stereotyping? How awareness of stereotyping prevalence impacts expression of stereotypes.

Abstract: The deleterious effects of stereotyping on individual and group outcomes have prompted a search for solutions. One approach has been to increase awareness of the prevalence of stereotyping in the hope of motivating individuals to resist natural inclinations. However, it could be that this strategy creates a norm for stereotyping, which paradoxically undermines desired effects. The present research demonstrates that individuals who received a high prevalence of stereotyping message expressed more stereotypes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(144 citation statements)
references
References 125 publications
1
139
1
3
Order By: Relevance
“…Simply increasing awareness of the ubiquity of stereotype-based bias has been shown experimentally to exacerbate the application of age, gender, and bodyweight stereotype-based bias. 71 Conversely, either informing participants that the prevalence of stereotype-based bias is low or that most people are trying to overcome the influence of stereotypes on their evaluations of others reduced the application of gender bias compared to no message or the message about the high prevalence of stereotype-based bias. 71 Building on this research, a simple intervention to study might involve randomly including such a message (e.g., “most NIH scientific peer reviewers are working hard to reduce the influence of stereotypes in their evaluation of R01s”) in the materials sent to a random sample of R01 reviewers.…”
Section: Discussionmentioning
confidence: 99%
“…Simply increasing awareness of the ubiquity of stereotype-based bias has been shown experimentally to exacerbate the application of age, gender, and bodyweight stereotype-based bias. 71 Conversely, either informing participants that the prevalence of stereotype-based bias is low or that most people are trying to overcome the influence of stereotypes on their evaluations of others reduced the application of gender bias compared to no message or the message about the high prevalence of stereotype-based bias. 71 Building on this research, a simple intervention to study might involve randomly including such a message (e.g., “most NIH scientific peer reviewers are working hard to reduce the influence of stereotypes in their evaluation of R01s”) in the materials sent to a random sample of R01 reviewers.…”
Section: Discussionmentioning
confidence: 99%
“…Highlighting women's agency may backfire for women who are less agentic as much as emphasizing communal traits for leaders has shown to hurt agentic women (Rudman & Glick, ). Furthermore, awareness about stereotypes may also increase stereotypic evaluations (Duguid & Thomas‐Hunt, ). Therefore, organizations should provide a balanced view of women and men that emphasizes that both men and women can be agentic and communal while providing accounts of women's agency and communality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, awareness about stereotypes may also increase stereotypic evaluations (Duguid & Thomas-Hunt, 2015). Therefore, organizations should provide a balanced view of women and men that emphasizes that both men and women can be agentic and communal while providing accounts of women's agency and communality.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Importantly, potential solutions to reducing assessor bias have shown mixed results. Large field experiments—all conducted outside a police recruitment context—have shown that blinding CVs may not lead to recruiting more individuals from underrepresented groups (Behaghel et al ); and implicit bias training does not seem to improve behaviour and may even backfire (Duguid and Thomas‐Hunt ). Public managers may therefore have to turn to the candidate experience to try to improve recruitment outcomes for people of colour or other underrepresented groups.…”
Section: Introductionmentioning
confidence: 99%